Molecular dynamics study of wetting of alkanes on water: from high temperature to the supercooled region and the influence of second inflection points of interfacial tensions. Issue 26 (29th June 2021) - Neupane, Pauf; Wilemski, Gerald
Abstract : Molecular dynamics simulations find unusual behavior of contact angle for alkanes on water at low temperatures. Abstract : To explore the wetting behavior of alkanes on bulk water interfaces, molecular dynamics (MD) simulations were carried out for united-atom PYS alkane models, and for SPC/E and TIP4P/2005 water models over a wide temperature range. The MD results at each temperature were used to find (1) the surface tension of the alkanes (octane, nonane) and water, and (2) the interfacial tensions of the alkane–water systems. These quantities were then used to calculate the spreading coefficient ( S ) and contact angle ( θ c ) for each alkane on water. At higher temperatures, the contact angle of octane and nonane on water is found to behave in accord with conventional expectations, i.e., it decreases with increasing temperature for both water models as each system approaches the usual high-temperature transition to perfect wetting. At lower temperatures, we found an unusual temperature dependence of S and θ c for each PYS alkane on SPC/E water. In contrast to conventional expectations, θ c decreases with a decrease in the temperature. For octane–SPC/E water, this unusual behavior of θ c occurs due to the presence of second inflection points (SIP) in the vapor–water and the octane–water interfacial tensions, whereas the SIP effect is much less important for the nonane–water system. The unusual temperature dependence of θ c observed for nonane on SPC/E water is also found for nonane on TIP4P/2005 water. On the other hand, such unusual wetting behavior has not been observed in the PYS octane–TIP4P/2005 water system, except possibly for the two lowest temperatures studied.